Contrast agent shell properties effects on heat deposition in bubble enhanced high intensity focused ultrasound - Gnanaskandan, Aswin (J Acoust Soc Am, 2021)
The effects of the viscoelastic shell properties of ultrasound contrast agents on heat deposition in bubble enhanced high intensity focused ultrasound (HIFU) are studied numerically using a model that solves the ultrasound acoustic field and the multi-bubble dynamics. The propagation of the nonlinear acoustic waves in the test medium is modeled using the compressible Navier-Stokes equations in a fixed Eulerian grid, while the microbubbles are modeled as discrete flow singularities, which are tracked in a Lagrangian fashion. These two models are intimately coupled such that both the acoustic field and the bubbles influence each other at each time step. The resulting temperature rise in the field is then calculated by solving a heat transfer equation applied over a much longer time scale than the computed high frequency dynamics. Three shell models for the contrast agent are considered, and the effect of each of these models on the heat deposition at the focus is studied. The differences obtained in the bubble dynamics results between the shell models are discussed. The importance of modeling the elasticity of the shell is addressed by comparing the results between Newtonian and non-Newtonian shell models. Next, a parametric study varying the shell properties is carried out, and the relative roles of the shell viscosity and elasticity in affecting the heat deposition are discussed. These observations are then used to give recommendations for the design of innovative contrast agents, specifically for the purpose of obtaining higher heat deposition in bubble enhanced HIFU.